B.N.Mityurova’s Role in Compiling Anthologies and Systematizing Source Base of History of Home Pedagogy - Cherednyak, Yuliya (Pedagogical Discourse, 2013)
This article analyses the role of B.N.Mityurova in systematizing source base of the history of home pedagogy and in compiling reading books on historical pedagogy, such as: «Readings on the history of Soviet pedagogy» (1961) «The anthology of educational thought of Ancient Rus’ and the Russian state, XIV-XVII centuries. (1985), «The anthology of educational thought Ukrainian Soviet Socialist Republic» (1988). It has been found that materials prepared by Professor B.N.Mityurov in anthologies on history of pedagogy, helped to systematize and summarize documents, literary and educational works which were recommended in the course «History of Education». Boris Nikiforovich’s parts of the works of teachers, social workers, and non popular authors were systematize. They are works of great value for the course and solves a number of problems in the history of pedagogy. It is proved that B.N.Mityurova’s contribution in systematization of information sources is great and helped to solve lots of problems.